Nigeria on the part of political and administrative sanity - Ugorji, Uzodinma Allwell (Lagos, Nigeria : Sibon Books, 2010)
Reveals that focused political leadership and sound administrative masterstroke will engender political and administrative sanity in Nigeria.
Includes bibliographical references.
oif 10/04/15
Loan
Keywords: Nigeria -- Politics and government